2010
DOI: 10.1002/jbm.a.32779
|View full text |Cite
|
Sign up to set email alerts
|

Topographical analyses of proliferation and differentiation of osteoblasts in micro‐ and macropores of apatite‐fiber scaffold

Abstract: A variety of calcium phosphates have been used for bone tissue-engineering applications. We developed porous hydroxyapatite (HAp) ceramics by firing green compacts consisting of spherical carbon beads and HAp fiber. The apatite-fiber scaffold (AFS) forms a three-dimensional network of fibers with two different pore sizes (micro- and macropores). In this study, we investigated cell distribution and fine cell structure in AFS by confocal laser scanning microscopy. Osteoblastic cells were permeated homogenously t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In the FT-IR spectra of the above Si-AFs, the absorptions assigned to the PO 4 3-groups at 1300-900, 600 and 570 cm -1 and assigned to the OH -group at 3570 cm -1 , were detected. In addition, the absorptions assigned to CO 3 2-groups were detected at 1460, 1420 and 880 cm -1 . These absorptions indicate that the present Si-AFs were consisted of carbonate-containing apatite.…”
Section: Fabrication Of Si-afsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the FT-IR spectra of the above Si-AFs, the absorptions assigned to the PO 4 3-groups at 1300-900, 600 and 570 cm -1 and assigned to the OH -group at 3570 cm -1 , were detected. In addition, the absorptions assigned to CO 3 2-groups were detected at 1460, 1420 and 880 cm -1 . These absorptions indicate that the present Si-AFs were consisted of carbonate-containing apatite.…”
Section: Fabrication Of Si-afsmentioning
confidence: 97%
“…As previously reported in [8], the Si-AFs were synthesized by a homogeneous precipitation method. Starting solution with a Ca/(P+Si) ratio of 1.67 was prepared by mixing Ca(NO 3 ) 2 4H 2 O, (NH 4 ) 2 HPO 4 , Si(OC 2 H 5 ) 4 (TEOS), (NH 2 ) 2 CO and HNO 3 . The concentrations of TEOS in the starting solution were 0 (AF), 0.8 (0.8Si-AF) and 1.6 mass% (1.6Si-AF).…”
Section: Synthesis Of Si-afsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 The AFS has excellent biocompatibility in vitro 54,56) and in vivo. 57,58) Using the AFS, we attempted to create tissue-engineered bone 54,55,59,60) as well as tissue-engineered liver.…”
Section: Creation Of a Novel Afs Using Single-crystal Hap Particles Wmentioning
confidence: 99%
“…10) Additionally, our recent study showed that AFSs can provide a three-dimensional culture environment and facilitate cell proliferation and differentiation using two different pores. 11) In recent years, mesenchymal stem cells (MSCs) have attracted much interest due to their self-renewing potential and multipotentiality for clinical use.…”
Section: )4)mentioning
confidence: 99%